The effect of executive walk rounds on nurse safety climate attitudes: A randomized trial of clinical units - Frankel Allan; Neilands Torsten B; Sexton J Bryan; Thomas Eric J; Helmreich Robert L (BMC, 2005)
Abstract Background Executive walk rounds (EWRs) are a widely used but unstudied activity designed to improve safety culture in hospitals. Therefore, we measured the impact of EWRs on one important part of safety culture - provider attitudes about the safety climate in the institution. Methods Randomized study of EWRs for 23 clinical units in a tertiary care teaching hospital. All providers except physicians participated. EWRs were conducted at each unit by one of six hospital executives once every four weeks for three visits. Providers were asked about their concerns regarding patient safety and what could be done to improve patient safety. Suggestions were tabulated and when possible, changes were made. Provider attitudes about safety climate measured by the Safety Climate Survey before and after EWRs. We report mean scores, percent positive scores (percentage of providers who responded four or higher on a five point scale (agree slightly or agree strongly), and the odds of EWR participants agreeing with individual survey items when compared to non-participants. Results Before EWRs the mean safety climate scores for nurses were similar in the control units and EWR units (78.97 and 76.78, P = 0.458) as were percent positive scores (64.6% positive and 61.1% positive). After EWRs the mean safety climate scores were not significantly different for all providers nor for nurses in the control units and EWR units (77.93 and 78.33, P = 0.854) and (56.5% positive and 62.7% positive). However, when analyzed by exposure to EWRs, nurses in the control group who did not participate in EWRs (n = 198) had lower safety climate scores than nurses in the intervention group who did participate in an EWR session (n = 85) (74.88 versus 81.01, P = 0.02; 52.5% positive versus 72.9% positive). Compared to nurses who did not participate, nurses in the experimental group who reported participating in EWRs also responded more favorably to a majority of items on the survey. Conclusion EWRs have a positive effect on the safety climate attitudes of nurses who participate in the walk rounds sessions. EWRs are a promising tool to improve safety climate and the broader construct of safety culture.